Micromalthus debilis LeConte, 1878 (Coleoptera: Micromalthidae), an American wood-boring beetle new to Italy - Ruzzier, Enrico; Colla, Andrea (Zootaxa, 2019)
Micromalthus debilis LeConte, 1878, an alien wood-boring beetle, is recorded for the first time in Italy and is recognized as a pest on wood structures of historical buildings in Europe.